Land and water resources management in the Caribbean - Paul, Compton L. and Jacob Opadeyi (eds) (Land and Water Resources Network, 2011)
Proceedings of the first Annual Technical Meeting of CLAWRENET held in Barbados, October 2000. Highlights various aspects of natural resources management in the region and proposes a planning framework for sustainable land and water use in SIDS.
Keywords: RESOURCES MANAGEMENT; SUSTAINABLE DEVELOPMENT; LAND USE; WATER UTILIZATION; CARIBBEAN